Bessie Coleman : first Black woman pilot - Plantz, Connie (Berkeley Heights, NJ : Enslow Publishers, 2001)
Describes the life of Bessie Coleman. Determined to open a flight school for other African Americans, "Brave Bessie" raised funds as a stunt pilot. Her life ended in a tragic accident, but not before her dream of flight made aviation history.
Includes bibliographical references (p. 124) and index.
Keywords: Coleman, Bessie, -- 1892-1926 -- Juvenile literature; Air pilots -- United States -- Biography -- Juvenile literature; African American women air pilots -- Biography -- Juvenile literature